The accidental superpower : the next generation of American preeminence and the coming global disorder - Zeihan, Peter (Twelve, 2014)
"In the bestselling tradition of The World Is Flat and The Next 100 Years, THE ACCIDENTAL SUPERPOWER will be a much discussed, contrarian and eye-opening assessment of American power. In THE ACCIDENTAL SUPERPOWER international strategist Peter Zeihan examines how geography, combined with demography and energy independence, will pave the way for one of the great turning points in history, and one in which America reasserts its global dominance. No other country has a greater network of internal waterways, a greater command of deepwater navigation, or a firmer hold on industrialization technologies than America. Zeihan argues that the future is undoubtedly bright for America, the only country with enough young adults to fill the capital-generating void that will be left behind by 2030. THE ACCIDENTAL SUPERPOWER also explores shale oil and its surprising key role in America's move towards energy independence and how it will shape (and is already shaping) American life for the next fifty years"--